Roles and Determinants of Banking Concentration in Jordanian Commercial Banks Profitability (Global Journal of Management and Business Research, 2014)
This study aimed to measure the effect of concentration to achieve the banking goal in each of (deposits and loans) on the profitability of the Jordanian commercial banks, which have been measured by using ratio of profitability (ROE). The study was conducted on Jordanian commercial banks. Also the study covered period between 1993 to 2013. The researcher used in this study descriptive analytical method and used statistical program (E-VIEWS) also data were analyzed by using simple linear regression method to test hypotheses of the study. The results showed that there was no statistically significant effect of the concentration of each of the banking (deposits and loans) on the profitability of commercial banks in Jordan. The study recommended the demand of Jordanian commercial banks to diversify the services provided by them and to rely on efficient and effective management of its reliance on more concentration to get market share.
Keywords: concentration; deposits; loans; banks; Jordan